PENGARUH CASH POSITION, DEBT TO ASSET RATIO DAN FIRM SIZE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Vina Vina; Jesslyn Kosasih; Kevin Susanto; Fuji Astuty (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
The purpose of this study is to determine and test the effect of Cash Position, Debt to Asset Ratio and firmsize on the Dividend Payout Ratio in Property and Real Estate companies listed on the Indonesia Stock Exchange for the period 2014-2018. This research is a quantitative research and the deductive approach is descriptive. The total population is 52 property & real estate companies on the IDX for the period 2014-2018. The sample technique uses purposive sampling so that the research sample that meets the criteria is as many as 13 companies. The data collection method used secondary data from financial reports, while the data analysis model was multiple regression. The results of the F test, namely Cash Position, Debt to Asset Ratio and Firm Size have an effect on the Dividend Payout Ratio. As individuals, Cash Position has a positive effect on the Dividend Payout Ratio, DAR has no effect on the Dividend Payout Ratio and Firm Size has a negative effect on the Dividend Payout Ratio. The value of determination coefficient as seen from Adjusted R2 is 0.435, which shows that the Dividend Payout Rate can be influenced by Cash Position, Debt to Asset Ratio and Firm Size of 43.5%, and 56.5% are other factors that are not shown in this research report.